Proceedings of the 6th Annual International Conference on Mobile Computing and Networking 2000
DOI: 10.1145/345910.345916
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of developing and deploying a context-aware tourist guide

Abstract: The GUIDE system has been developed to provide city visitors with a hand-held context-aware tourist guide. The system has been successfully deployed in a major tourist destination and is currently at the stage where it is publicly available to visitors who wish to explore the city. Reaching this stage has been the culmination of a number of distinct research efforts. In more detail, the development of GUIDE has involved: capturing a real set of application requirements, investigating the properties of a cell-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
210
0
5

Year Published

2002
2002
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(215 citation statements)
references
References 10 publications
0
210
0
5
Order By: Relevance
“…The system has been successfully deployed in a tourist setting and used over a period of four weeks by 60 people [9]. The major conclusions from the study were that visitors found the location-aware navigation and information retrieval mechanisms both useful and reassuring; and that the majority of visitors appreciated that the system were aware of their location to within a certain area.…”
Section: Related Workmentioning
confidence: 96%
See 2 more Smart Citations
“…The system has been successfully deployed in a tourist setting and used over a period of four weeks by 60 people [9]. The major conclusions from the study were that visitors found the location-aware navigation and information retrieval mechanisms both useful and reassuring; and that the majority of visitors appreciated that the system were aware of their location to within a certain area.…”
Section: Related Workmentioning
confidence: 96%
“…for tagging [22], for displaying context information, like location [15], or for displaying relevant information in a specific context [9]. There are no examples reported on the use of 'active' use of context information for automatically triggering actions or services.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Projects such as GUIDE [7] and Cyberguide [8] addressed the use of information about location and situation to guide the user when visiting tourist attractions.…”
Section: Related Workmentioning
confidence: 99%
“…With respect to sensors, the vest prototype includes more sensors than the backpack. We used a sound sensor 7 , a temperature sensor 8 , a light sensor 9 , a humidity sensor 10 and a 3-axis accelerometer 11 , all wired to the sensor node. In addition to these, there are three other sensors being used, two that are internal to the smartphone -the internal accelerometer and a virtual time sensor to provide the time of day -and one external bluetooth GPS receiver 12 node.…”
Section: Sensors and Prototypementioning
confidence: 99%